Families of patients in ICU: A Scoping review of their needs and satisfaction with care. Issue 3 (18th May 2019) - Scott, Pamela; Thomson, Patricia; Shepherd, Ashley
Abstract: Aim: To describe published literature on the needs and experiences of family members of adults admitted to intensive care and interventions to improve family satisfaction and psychological well‐being and health. Design: Scoping review. Methods: Several selective databases were searched. English‐language articles were retrieved, and data extracted on study design, sample size, sample characteristics and outcomes measured. Results: From 469 references, 43 studies were identified for inclusion. Four key themes were identified: (a) Different perspectives on meeting family needs; (b) Family satisfaction with care in intensive care; (c) Factors having an impact on family health and well‐being and their capacity to cope; and (d) Psychosocial interventions. Unmet informational and assurance needs have an impact on family satisfaction and mental health. Structured written and oral information shows some effect in improving satisfaction and reducing psychological burden. Future research might include family in the design of interventions, provide details of the implementation process and have clearly identified outcomes.